2017
DOI: 10.1182/bloodadvances.2017011957
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell metabolism in Down syndrome: hints on metabolic derangements in aging

Abstract: Key Points• The red blood cell metabolic signature of Down syndrome is identified• Trisomy 21 impacts red blood cell redox, amino acid, purine, and bile acid metabolism in an age-and sexdependent fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…In contrast, other metabolites associated with hypercoagulability, such as homocysteine (65) (which increases in Down syndrome, ref. 66), were decreased in patients with COVID-19. The latter may be explained by increased oxidant stress in patients with COVID-19, suggested by increased serum levels of methionine sulfoxide and cystine, along with decreased antioxidants, such as cysteine and taurine (67) (but, interestingly, not reduced glutathione).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 87%
“…In contrast, other metabolites associated with hypercoagulability, such as homocysteine (65) (which increases in Down syndrome, ref. 66), were decreased in patients with COVID-19. The latter may be explained by increased oxidant stress in patients with COVID-19, suggested by increased serum levels of methionine sulfoxide and cystine, along with decreased antioxidants, such as cysteine and taurine (67) (but, interestingly, not reduced glutathione).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 87%
“…As already mentioned earlier, DS is characterized by an overexpression of genes on chromosome 21, in addition to an overall dysregulation of an even larger set of genes located on the other chromosomes (Letourneau et al 2014 ; Araya et al 2019 ; Culp-Hill et al 2017 ; Mao et al 2005 ). Among these, there are genes involved in oxidative phosphorylation (OXPHOS), including all five mitochondrial complex subunits, genes implicated in mitochondrial biogenesis, and more generally in the mitochondrial function.…”
Section: Gene Expression Proteomic and Metabolomic Profiling Of Ds Amentioning
confidence: 91%
“…Culp-Hill et al ( 2017 ) reported untargeted and targeted metabolomics datasets. Data were filtered for the age: 12 ≤ Age ≤ 54, in line with the original study.…”
Section: Gene Expression Proteomic and Metabolomic Profiling Of Ds Amentioning
confidence: 99%
“…In the last few years, the advent of omics technologies revived interest around blood metabolism as a critical source of information to investigate derangements in system metabolism as a function of aging [29]. Recently, we reported the impact of aging on RBC metabolism in a cohort of 97 subjects, including individuals with Down syndrome, the most common human condition due to aneuploidy in the human population (one in ~700 live births in the United States) [30]. Of note, individuals with Down syndrome are more susceptible to several of the comorbidities associated with aging, including neurocognitive diseases (e.g., Alzheimer’s disease), several autoimmune and hematological cancers, pulmonary hypertension, and hearing and vision problems [31,32].…”
Section: Introductionmentioning
confidence: 99%